HUBUNGAN PANJANG BOBOT DAN FAKTOR KONDISI IKAN ENDEMIK PIRIK (Lagusia micracanthus, Bleeker 1860) DI SUNGAI SANREGO, SULAWESI SELATAN - Nur, Muhammad; Dahlan, Muh. Arifin (Torani Journal of Fisheries and Marine Science, 2015)
This research aimed to study correlation between the weight length and the condition factor of Pirikfish.The sample collection conducted from September 2014 through February 2015 in Sanrego river, LangiVillage, Bone regency, South Sulawesi. The analysis of the samples carried out in the Laboratory of FishBiology, Department of Fisheries, Hasanuddin University, Makassar. The total length was measured usingdigital calliper of 0.01 mm and the weight was measured using the digital scale of 0.001 g. The fish sampleswere dissected and categorized into male and females with the sex gonad maturity. The total samples of theendemic pirik fish collected during the research were 162, 72 male dan 90 female fish. The correlation of theweight length was based on the equation W=0,00003L2,8719 at male fish, W=0,00003L2,8575 in the female fish andin general, the obtained equation was W=0,00003L2,8846. The result of the t test showed that the value washigher than t table; therefore, the Pirik fish in Sanrego rivers had negative allometric growth attern (minor) (b <3), since the addition of body length was faster than the increase of body weight. The analysis of the conditionfactor revelead that the value range of 0,8038-1,2926 with an average 1,0274 in male fish and 0,9263-1,4533with the average of 1,1598 in female fish. This showed that the conditions factors of the endemic pirik fish werelower compared to the female fish.Keywords : Length weight, condition factor, endemic-pirik fish, Sanrego River, South Sulawesi